The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1186/s13256-017-1517-7
|View full text |Cite
|
Sign up to set email alerts
|

Six-year survival of reimplanted talus after isolated total talar extrusion: a case report

Abstract: BackgroundOpen total extrusion of the talus without concomitant fracture is an extremely rare injury. We present 6-year follow-up data of a patient treated using a temporary spanning external fixator and less invasive single K-wire fixation.Case presentationA 55-year-old Asian man who had a totally extruded talus without fracture underwent immediate reimplantation surgery. A spanning external fixator with single antegrade K-wire fixation was applied to maintain the reimplanted talus. During 6 years of follow-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 24 publications
0
14
0
1
Order By: Relevance
“…Kwak, et al reported revascularisation of a completely extruded talus with serial MRI scans after prompt reimplantation. They did not report any soft tissue problems in achieving the desired outcome [30]. A systemic review in 2015 reporting on 39 articles with 86 cases showed that 84% had open injuries and 12% had associated fractures other than talus.…”
Section: Discussionmentioning
confidence: 99%
“…Kwak, et al reported revascularisation of a completely extruded talus with serial MRI scans after prompt reimplantation. They did not report any soft tissue problems in achieving the desired outcome [30]. A systemic review in 2015 reporting on 39 articles with 86 cases showed that 84% had open injuries and 12% had associated fractures other than talus.…”
Section: Discussionmentioning
confidence: 99%
“…The failure of the medial bony stabilizer allows talus extrusion. In most of the reported cases, it remained attachments, especially deltoid ligament 2,6 . There was no strong evidence-based procedure.…”
Section: Complete Tte and Medial Malleolusmentioning
confidence: 96%
“…Liegt eine nicht zu rekonstruierende Zertrümmerung des Talus vor, so sollte trotzdem keine primäre Astragalektomie, sondern eine Erhaltung im Sinne einer primären oder frühsekundären Arthrodese des oberen und unteren Sprunggelenkes angestrebt werden. Dies gilt auch für die traumatische Talusextrusion, nach der dieser primär im Sinne eines "Spacers" wieder eingebracht werden kann [29,30].…”
Section: Merkeunclassified